UKRAINIAN AND ENGLISH VERBS: BILATERAL CONTRASTIVE CROSS-LINGUISTIC PERSPECTIVE - Natalia Ivanytska; Nina Ivanytska (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2018)
The paper focuses on the contrastive analysis procedure from the bilateral perspective. This work is relevant due to current cross-linguistic approaches aimed at the comprehensive study of the notional words being the central ones with their ability to express a variety of categorical meanings. The verb is viewed as a central word in Ukrainian and English being of scholars' interest for a long time. Bilateral contrastive study is believed to be an effective tool for identifying similarities and differences within the subsystems of Ukrainian and English verbs. The authors present grounds for revealing a number of benefits of comparing language units from bilateral perspective. The two-way contrastive analysis is considered to be scientifically valid when using a reasonable tertium comparationis. The latter is viewed as an objective extra-lingual basis that has a specific realisation in each language. When studying verb's systems as complicated language items the choice of tertium comparationis turns next to a verb's category "process". The predominant advantage of this category is accounted for its universal, cross functional, broad-based nature. Comprising semantic and grammatical aspects, the category of "process" is believed to be a key point for building semantic and syntagmatic paradigms in the verb's system. The study concludes that the category of "process" is qualified as generalised construct (model) comprising lexical semantics of verbs, and a set of grammatical (morphological, derivational, syntactic) categories. The realisation of verbal processing is represented by the unique combinations of forms in each of the compared languages. The specificity of the verb's category of "process" in the compared languages reveals the hidden facts that are believed to enrich the theory of language with new generalisations.